Brechas salariales por etnia y ubicación geográfica en Santiago de Cali - Jhon James Mora; Andrés Mauricio Arcila (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2014)
– In this article we estimate the wage gap between white people and Afro-American people in Cali by using data from the survey of employment and quality of life of 2013. The estimation is weighted by the number of individuals that recognize themselves as Afro-American as a measure of statis- tical correction given the disaggregation of the data, and our approach lets us including the spatial location in the censure process. Our results show that including variables such as migrations and discrimination perception in the participation equation for Afro-Americans, the wage gap is about 43%, where 9% is associated to explained characteristics by differences in human capital and 33% remains associated with labor discrimination.
Keywords: J31; J71; R23; 330; wage gap; Oaxaca-Blinder; Afro-descendant; wage decomposition